Factors Affecting Students’ Achievement Motivation in Private Colleges of Kathmandu Valley - Thapa, Utsaha; Dhakal, Shilpa (Journal of Business and Social Sciences Research, 2023)
This research study aims to examine the factors affecting students’ achievement motivation with a sample size of 104 students from 37 private colleges in Kathmandu. The study followed a cross-sectional research design, where the structured questionnaire was distributed online and offline, and the data were analysed using multiple regression. The results showed positive classroom relationship as the factor most influencing the students’ achievement motivation and should be considered. In a nutshell, this study identified the possible factors for student achievement motivation that might help develop strategies for improving the student’s academic performance.